2015
DOI: 10.1177/0884533615622639
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Perioperative Nutrition in Pediatric Populations

Abstract: Nutrition status prior to surgery and nutrition rehabilitation after surgery can affect the morbidity and mortality of pediatric patients. A comprehensive approach to nutrition in pediatric surgical patients is important and includes preoperative assessment, perioperative nutrition considerations, and postoperative recovery. A thorough nutrition assessment to identify patients who are at nutrition risk prior to surgery is important so that the nutrition status can be optimized prior to the procedure to minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 55 publications
(100 reference statements)
3
22
0
3
Order By: Relevance
“…Above gastrointestinal physiological changes are beneficial to promote the recovery of gastrointestinal function and shorten the time of exhaust and defecation. In recent years, studies have shown that early feeding after general anesthesia does not increase the incidence of postoperative complications such as nausea, vomiting, and abdominal distension [17], which is basically consistent with our results. In this paper, we found that eating 2 hours after surgery did not increase the incidence of nausea/vomiting.…”
Section: Analysis Of the Feasibility Of Early Feeding After Tracheal supporting
confidence: 93%
“…Above gastrointestinal physiological changes are beneficial to promote the recovery of gastrointestinal function and shorten the time of exhaust and defecation. In recent years, studies have shown that early feeding after general anesthesia does not increase the incidence of postoperative complications such as nausea, vomiting, and abdominal distension [17], which is basically consistent with our results. In this paper, we found that eating 2 hours after surgery did not increase the incidence of nausea/vomiting.…”
Section: Analysis Of the Feasibility Of Early Feeding After Tracheal supporting
confidence: 93%
“…We found that overweight children experienced a shorter LOS, which may be due to residual confounding, such that overweight may confer a benefit to withstand the stressors of operative intervention in children with ESLD not accounted for by the covariates in our model. Although our findings should be interpreted cautiously given the challenges in using weight as a marker of malnutrition for individuals with ESLD and potential ascites, our findings in underweight and obese recipients suggest that multidisciplinary teams should focus their efforts on optimizing the nutritional status of underweight recipients in a clinical setting, aiming to correct any nutritional deficiencies prior to operative intervention and improve post‐operative outcomes 37,38 . Underweight infants in our study experienced a longer LOS, which may be due to a more gradual return to enteral nutrition in this young age group.…”
Section: Discussionmentioning
confidence: 71%
“…Many children with SRS also have abnormal tooth distribution and a small mandible, which affects airway visualization and intubation 95 . Finally, young children with SRS who are malnourished might not heal well following surgery 96 . [97][98][99][100][101] .…”
Section: Surgery and Anaesthesiamentioning
confidence: 99%